ANALISIS PEMAHAMAN PEPATAH HAKKA TERHADAP MAHASISWAPROGRAM STUDI PENDIDIKAN BAHASA MANDARINUNIVERSITAS TANJUNGPURA - Veny, Veny; Veronica, Tjen; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Hakka proverbs is the crystallization of Hakka-language art, and its also a bearer of traditional Hakka culture. In general, proverbs are used to giving satire, reprimand, and advice, because a proverbcontains moral values, norms, advice and parables. The purpose of this paper is to find out and study the conditions of understanding inusing the Hakka proverbs by student of Chinese Language EducationStudy Program, Teacher Training and Education Faculty, Tanjungpura University. The research in this paper is using test questions and questionnaires to get the result if this research. The results of the research stated that the students mastery of the Chinese Language Education Study Program, Teacher Training andEducation Faculty, Tanjungpura University class of 2019, 2020, 2021, and 2022 towards Hakka proverbs was relative good, this indicated that they quite understood the Hakka proverbs. The type of Hakka proverb that was most mastered by students was about "environmental/social proverb" which reached 82.17%, while those that were less mastered were about "artificial proverb" which onlyreached 78.86%. After analyzing, the writer realizes that the students already have basic knowledge about Hakka proverbs, but they rarelyuse Hakka proverbs, so there are some proverbs they have forgottenand do not understand the meaning of these Hakka proverbs.